Synthesis and Evaluations of Novel Apocynin Derivatives as Anti-Glioma Agents - Yang, Tao; Zang, Da-Wei; Shan, Wei; Guo, An-Chen; Wu, Jian-Ping; Wang, Yong-Jun; Wang, Qun (Frontiers in Pharmacology, 2019)
Apocynin (4-hydroxy-3-methoxyacetophenone) is a natural polyphenolic compound with multiple biological activities. In the present study, a series of apocynin derivatives were designed and synthesized. The in silico ADMET prediction, blood-brain barrier (BBB) penetration assay, anti-NADPH-oxidase activity, reactive oxygen species (ROS) levels, and anti-glioma effects of these apocynin derivatives were evaluated. The anti-glioma mechanisms of candidate compounds were studied by ﬂow cytometer and western blot. The results showed that D31 exhibited higher BBB penetration, increased ROS generations and significant anti-glioma effects both in vitro and in vivo. Further studies showed that D31 inhibited the activations of NF-κB pathway. Overall, our data demonstrated that D31 inhibited growth and induced apoptosis of glioma, which might be caused by ROS related NF-κB activation. The current study suggested that D31 could be further explored for its potential use in anti-glioma therapy.